Consumer Purchase Decisions on Food and Beverage Delivery Services on the GoFood Application - Muhammad Saputra; Cahyani Pratisti; Novita Sari; Niken Paramitasari (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Abstract—This study aims to determine the effect of price discounts and online customer ratings on consumer decisions to use GoFood aplication for food and beverage delivery services. This type of research was associative qualitative research. The sampling method used non-probability sampling with a purposive sampling technique and 140 respondents obtained. The data analysis method used Partial Least Square (PLS). The results indicated that both partial or simultan the price discount and online customer ratings affect the consumer purchasing decisions on food and beverage delivery services on the GoFood application.Keywords— Price discount, Online customer ratings, Purchase decision